Exploring Ultrasound and Microwave-Assisted Accelerated Aging of Jerez Vinegar: Impacts on Phenolic, Volatile, Colorimetric, and Sensory Properties - Uysal, Reyhan Selin; Issa-Issa, Hanan; Carbonell-Barrachina, Angel A.; Sendra, Esther (Mdpi, 2025)
Jerez vinegar is a high-quality wine vinegar produced in the Vinagre de Jerez denomination of origin (Spain) and is traditionally aged in wood barrels for over 10 years. Considering the long aging process, a practical technique to accelerate the aging process was simulated. This study aimed to evaluate ultrasound and microwave treatments as alternative aging methods for fresh Jerez vinegars with oak chips, and to investigate their effects on phenolic content, volatile compounds, and colorimetric and sensory properties. Fresh control samples with oak chips were treated using ultrasound (US) in an ultrasonic bath three times: 0.5 h (US1), 2 h (US2), and 10 h (US3). Microwave (MW) treatments were performed using a domestic microwave oven with three power/time combinations: 640 W for 10 min (MW1), 640 W for 20 min (MW2), and 800 W for 10 min (MW3). Compared with the fresh control (4230 mu g/kg), US- and MW-treated samples showed a significant reduction in total phenolic content, decreasing to 3943 mu g/kg in the US1 sample and to 3988 mu g/kg in the MW2 treatment. Moreover, volatile substances significantly decreased from 1019 mg/L in the fresh control to 623 mg/L in the US3 treatment and 716 mg/L in the MW1 sample. Regarding sensory properties, US3 and MW1 treatments exhibited marked distinctions in certain odor and flavor attributes when compared with the fresh control. As a result, both techniques modified the phenolic, volatile and sensory profiles. Further research is needed to fully mimic the aging process, but US has proven to be a promising technique.
Keywords: Sherry Vinegar; Ultrasonic Field; Microwave Field; Fast Aging; Lc-Ms/Ms; Gc-Ms; Sensory Profile; Chromatic Properties